Context influences preference for and level of physical activity of adolescents with intellectual and developmental disabilities. Issue 3 (4th June 2019) - Pincus, Shari M.; Hausman, Nicole L.; Borrero, John C.; Kahng, SungWoo
Abstract : The purpose of the current study was to replicate and extend Hustyi, Normand, Larson, and Morley (2012) by determining the effects of different contexts on physical activity displayed by adolescents with intellectual and developmental disabilities, and determining preference for various activities. Results indicated that an exergaming condition produced the highest levels of activity. Results of a preference assessment indicated that 2 out of 3 participants preferred the physical activity context to the sedentary. For the third participant, an intervention was included to increase activity. Although the intervention was successful, participant preference for the sedentary activity context remained unchanged.